ASUHAN KEPERAWATAN PADA NY.M G2P1A0 TRIMESTER 1 DENGAN EMESIS GRAVIDARUM DI WILAYAH CILANGKAP JAKARTA TIMUR - Wulan Trisnawati (2023)
Background: Nausea and vomiting (Emesis gravidarum) is a common condition during the first trimester of pregnancy caused by an increase in the hormones estrogen and Human Chorionic Gonadrotropin (HCG). Emesis gravidarum can have a negative impact on pregnant women, for example, such as decreased appetite, weight loss and dehydration. Emesis gravidarum can be caused by several other factors such as poor diet, lack of rest and sleep and stress. This research was conducted to find out emesis gravidarum and the right way of handling it for sufferers through nursing care for pregnant women with emesis gravidarum. Methods: This research was conducted using the case study method of nursing care for Mrs. M with emesis gravidarum in the Cilangkap area, East Jakarta from 26 February to 28 February 2023. Data collection was carried out by means of interviews, observation and documentation. Results: Nursing diagnoses on the problem Ny. M is Nausea related to pregnancy. Nursing interventions carried out in the form of identifying factors that cause vomiting, reduce or eliminate conditions that cause vomiting, teach the use of non-pharmacological techniques to manage vomiting. Nursing implementation is carried out in accordance with nursing interventions that have been made and nursing evaluations are carried out. Within 3x24 hours the problem of nausea in Mrs. M can be resolved. Conclusion: Nursing care given to Mrs. M can be resolved and Mrs. M can intervene independently.